2013
DOI: 10.1002/chem.201303602
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Ionic Liquid Based on Tetrachloroferrate Exhibits Three‐Dimensional Magnetic Ordering: A Combined Experimental and Theoretical Study of the Magnetic Interaction Mechanism

Abstract: A new magnetic ionic liquid (MIL) with 3D antiferromagnetic ordering has been synthetized and characterized. The information obtained from magnetic characterization was supplemented by analysis of DFT calculations and the magneto-structural correlations. The result gives no evidence for direct iron-iron interactions, corroborating that the 3D magnetic ordering in MILs takes place via super-exchange coupling containing two diamagnetic atoms intermediaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 57 publications
9
67
0
Order By: Relevance
“…The peaks at n s ¼ 110 and n as ¼ 135 cm À1 are attributed to the bending modes and the other two, n s ¼ 332 and n as ¼ 338 cm À1 , respectively are related to the stretching modes of the Fe-Cl bond. This agrees with ndings in Emim[FeX 4 ] (T N : 4.2 K for X ¼ Cl and 12.5 K for X ¼ Br) 38,51 and Dimim[FeX 4 ] (T N : 5.6 K for X ¼ Cl and 7.7 K for X ¼ Br) 40,41 paramagnetic ILs. 6 and Table 4) of Edimim [FeCl 4 ] are assigned to the Edimim + cation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The peaks at n s ¼ 110 and n as ¼ 135 cm À1 are attributed to the bending modes and the other two, n s ¼ 332 and n as ¼ 338 cm À1 , respectively are related to the stretching modes of the Fe-Cl bond. This agrees with ndings in Emim[FeX 4 ] (T N : 4.2 K for X ¼ Cl and 12.5 K for X ¼ Br) 38,51 and Dimim[FeX 4 ] (T N : 5.6 K for X ¼ Cl and 7.7 K for X ¼ Br) 40,41 paramagnetic ILs. 6 and Table 4) of Edimim [FeCl 4 ] are assigned to the Edimim + cation.…”
Section: Resultssupporting
confidence: 86%
“…Importantly, in ILs based on imidazolium cation with paramagnetic anions, such as the presented compounds, it is also necessary to investigate other non-bonding interactions, like halogen-halogen 35 (between the nearest metal complex anions) or anion-p 36 (between the anion and cation) as these interactions play an important role in the organization of their structural units. Our results reveal that (i) halogenhalogen interactions are the main force inducing the 3D magnetic ordering in the solid state of this type of ILs 40 (ii) the spin population in the metal complex anion together with the distances and angles between the superexchange pathways [Fe-X/X-Fe (X ¼ halide)] play a decisive role in attaining the 3D magnetic ordering 40 and (iii) a less electronegative halide ion rises the efficiency of the magnetic couplings. 37,38 Moreover, changing the external conditions, such as pressure, shows an inuence in the magnetic coupling, such as in Emim [FeCl 4 ], which vary from antiferromagnetic (AF) to ferrimagnetic ordering.…”
Section: Introductionmentioning
confidence: 89%
“…It has previously been reported that in metal salts of this kind 3-dimensional ordering can occur at low temperature through superexchange coupling via two diamagnetic intermediaries [27]. .…”
Section: Magnetic Properties Of the Bulk Surfactants Studied Via Squimentioning
confidence: 99%
“…They exhibit interesting properties such as low vapour pressures, high thermal stability, large electrochemical windows, and have unique solvent properties which are proving useful for many separation processes [16]. ILs containing transition metals had been known for some time [17,18] but it had always been assumed that the metallic centers were isolated, lacking long-range interactions and communication necessary to be magnetically active [19]. Hayashi et al reported …”
Section: Magnetic Ionic Liquid Surfactants -Classmentioning
confidence: 99%
“…Subsequently, after experimental confirmation that [emim][FeCl4] showed 3-dimensional ordering below 4K, magnetic interactions were reconsidered [21]. More recently, García-Saiz et al showed that superexchange coupling could occur via two diamagnetic intermediaries [19].…”
Section: Magnetic Ionic Liquid Surfactants -Classmentioning
confidence: 99%